2013
DOI: 10.1128/jvi.02139-12
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin-Resistant Mutants of Human Enterovirus 71 Express a High Replication Fidelity Phenotype during Growth in Cell Culture

Abstract: It has been shown in animal models that ribavirin-resistant poliovirus with a G64S mutation in its 3D polymerase has high replication fidelity coupled with attenuated virulence. Here, we describe the effects of mutagenesis in the human enterovirus 71 (HEV71) 3D polymerase on ribavirin resistance and replication fidelity. Seven substitutions were introduced at amino acid position 3D-G64 of a HEV71 full-length infectious cDNA clone (26M). Viable clone-derived virus populations were rescued from the G64N, G64R, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
72
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 39 publications
6
72
1
Order By: Relevance
“…For example, by using different strains of FMDV, one study identified one substitution (M296I) while other independent studies identified three (P44S, P169S and M296I) or four (D5N, A38V, M194I and M296V) different substitutions that confer resistance to ribavirin and increased fidelity (Agudo et al, 2010;Sierra et al, 2007;Zeng et al, 2014). A couple of amino acid mutations were also identified in coxsackievirus B3 virus, human enterovirus 71 virus and bovine viral diarrhea virus (Curti & Jaeger, 2013;Gnädig et al, 2012;Sadeghipour et al, 2013). For the two amino acid substitutions identified in PRRSV in this study, when they were introduced into the PRRSV VR2385 infectious clone backbone, the rescued reconstituted virus vA283T showed a more ribavirin-resistant profile and fewer quasispecies variants than the other reconstituted virus vH421Y (Fig.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…For example, by using different strains of FMDV, one study identified one substitution (M296I) while other independent studies identified three (P44S, P169S and M296I) or four (D5N, A38V, M194I and M296V) different substitutions that confer resistance to ribavirin and increased fidelity (Agudo et al, 2010;Sierra et al, 2007;Zeng et al, 2014). A couple of amino acid mutations were also identified in coxsackievirus B3 virus, human enterovirus 71 virus and bovine viral diarrhea virus (Curti & Jaeger, 2013;Gnädig et al, 2012;Sadeghipour et al, 2013). For the two amino acid substitutions identified in PRRSV in this study, when they were introduced into the PRRSV VR2385 infectious clone backbone, the rescued reconstituted virus vA283T showed a more ribavirin-resistant profile and fewer quasispecies variants than the other reconstituted virus vH421Y (Fig.…”
mentioning
confidence: 86%
“…The results indicated that PRRSV is highly sensitive to ribavirin, since it accumulates more lethal mutations by mistakenly incorporating ribavirin. For other RNA viruses, it has been reported that poliovirus can tolerate consecutive in vitro passages at 600 mM ribavirin, foot-mouth disease virus (FMDV) at 800 mM, and human enterovirus 71 at 1600 mM (Sadeghipour et al, 2013;Sierra et al, 2007;Vignuzzi et al, 2006). The high sensitivity of PRRSV to ribavirin suggested a potential usage as an antiviral to inhibit PRRSV infection (Kim & Lee, 2013).…”
mentioning
confidence: 99%
See 3 more Smart Citations